Application of independent‐left‐and‐right‐wheel‐driving force controller to torque vectoring differential with two‐input‐two‐output motor drive system for electrified vehicles. Issue 4 (5th September 2022) - Fuse, Hiroyuki; Fujimoto, Hiroshi; Sawase, Kaoru; Takahashi, Naoki; Takahashi, Ryota; Okamura, Yutaro; Koga, Ryosuke
Abstract: A torque‐difference‐amplification torque vectoring differential (TDA‐TVD), which is composed of a two‐input‐two‐output system, has a great potential for cornering maneuverability; however, the overall controllability of slip ratio or driving force control is difficult owing to its complex mechanical structure. In order to enhance the controllability of TDA‐TVD, this study proposes a design method to apply a driving force controller (DFC) with a decent slip ratio and driving force controllability, which was originally intended for independent wheel drive systems. An experimental verification on a slippery road using a real vehicle with the TDA‐TVD indicated that the DFC can be applied to the TDA‐TVD and that it improves the overall performance of the traction control.